IMPACT POLITIQUE ET TERRITORIAL DE LA ROUTE BITUMÉE BONDOUKOU-BOUNA AU NORD-EST DE LA CÔTE D’IVOIRE - Lazare, Atta Koffi; Téré, Gogbe; Joseph, Kra Kouadio (European Scientific Journal, ESJ, 2014)
The weakness of the public investments in the north-east of Côte d’Ivoire has made this region the most deprived and marginalized area of the country. Isolated from the other part of the country, the north-eastern, especially the region of Bouna is regarded as no man’s land, a penitentiary, a prison for the recalcitrant civil servants. Due to the numerous problems of development faced, the region differed completely from the other regions of the country. The populations of this area had feeling that they were not member of the nation in construction. But, since 1997, when the government has tarred the road from Bondoukou to Bouna, the population’s feeling of being member of the nation has increased. From them, this tarred road is an evidence of their citizenship. It has not only reinforced their feeling of being member of the nation but it has also permitted to bring local governance to the doorsteps of the people and enhance decentralization process in the region. It is a political road, a road of national unity, food security and economic defence road in that political context influenced by the concept of " ivoirité ".